Penggunaan Kulit Pisang pada Proses Pemurnian Minyak Esensial Kulit Buah Jeruk Pontianak - Welly Deglas (Program Studi Teknologi Hasil Pertanian, 2023)
This study aims to investigate the effect of using banana peels in the process of refining Pontianak orange peel essential oil and to assess the effect of soaking time on banana skin yield, clarity value, and quality of Pontianak orange peel essential oil. Completely randomized design (CRD) method with four different treatments, namely soaking time of banana peels for 1 day, 2 days, 3 days, and 4 days, was used in this study with three repetitions. The results showed that the longer the banana peel soaked in orange peel essential oil, the turbidity level of the oil decreased significantly. The highest turbidity was recorded at 37 NTU, while the lowest turbidity reached 17 NTU. The organoleptic test results for clarity, color, and aroma showed significant differences between the samples, which can be seen from the calculated F value which is greater than the table F value at a significance level of 5% and 1%.